Expression Characteristics and Prognostic Study of PPP1R13L in Brain Metastases of Lung Adenocarcinoma. - LIU, Luyao; FAN, Peiwen; CHANG, Cheng; WANG, Ruozheng (Chinese Journal of Lung Cancer, 2025)
Background and objective Lung adenocarcinoma is prone to brain metastasis, and the prognosis of patients is extremely poor. The inhibitor of apoptosis-stimulating protein of p53 (iASPP) protein, encoded by the protein phosphatase 1 regulatory subunit 13-like (PPP1R13L) gene, is a key inhibitor of the p53 pathway and promotes carcinogenesis in various tumors, but its role in brain metastasis of lung adenocarcinoma is unknown. This study aims to analyze the tumor microenvironment characteristics of patients with brain metastasis of lung adenocarcinoma and explore the expression of PPP1R13L in brain metastasis tissues and its clinical significance by single-cell sequencing and clinical sample analysis. Methods Brain tissues from 4 patients with lung adenocarcinoma brain metastasis and 2 patients with oligodendroglioma (ODG) were collected from the Affiliated Tumor Hospital of Xinjiang Medical University from January 2014 to December 2024 for single-cell sequencing. The tumor microenvironment was analyzed by combining single-cell sequencing data from 4 lung adenocarcinoma samples and 4 normal lung tissue samples from public databases. Additionally, clinical data and paraffin sections of 50 patients with lung adenocarcinoma brain metastasis in this hospital were collected, and immunohistochemistry was used to assess iASPP expression and its association with clinicopathologic features and patient outcome. Results Compared with the ODG and lung adenocarcinoma groups, the specific epithelial cells in the lung adenocarcinoma brain metastasis group were mainly enriched in oxidative phosphorylation, apoptosis, hypoxia, and p53 pathways. PPP1R13L, as an upregulated differential gene, was highly expressed in the specific epithelial cell subpopulation of the brain metastasis group; the interaction between PPP1R13L-positive cells and fibroblasts was significant, activating cell-matrix adhesion related pathways, with the key ligand-receptor pair being collagen type I alpha 1 chain-cluster of differentiation 44 (COL1A1-CD44). Statistical evaluation revealed that smoking (HR=2.543, 95%CI: 1.159-5.583, P=0.020) and high expression of iASPP (HR=3.351, 95%CI: 1.310-8.575, P=0.012) were independent predictors of poor prognosis in lung adenocarcinoma patients with brain metastases. Conclusion This study revealed the interaction between epithelial cells and fibroblasts in the microenvironment of lung adenocarcinoma brain metastasis and implicate PPP1R13L as a potential prognostic indicator and actionable target, offering rationale for precision therapy against lung adenocarcinoma brain metastases.